Estimation of the P Fertilizer Demand of China Using the LePA Model - Yu, Wenjia; Li, Haigang; Nkebiwe, Peteh Mehdi; Li, Guohua; Müller, Torsten; Zhang, Junling; Shen, Jianbo (Frontiers in Environmental Science, 2021)
Modern phosphate (P) fertilizers are sourced from P rock reserves, a finite and dwindling resource. Globally, China is the largest producer and consumer of P fertilizer and will deplete its domestic reserves within 80 years. It is necessary to avoid excess P input in agriculture through estimating P demand. We used the legacy P assessment model (LePA) to estimate P demand based on soil P management at the county, regional, and country scales according to six P application rate scenarios: (1) rate in 2012 maintained; (2) current rate maintained in low-P counties and P input stopped in high-P counties until critical Olsen-P level (CP) is reached, after which rate equals P-removal; (3) rate decreased to 1–1.5 kg ha−1 year−1 in low-P counties after CP is reached and in high-P counties; (4) rate in each county decreased to 1–8 kg ha−1 year−1 after soil Olsen-P reached CP in low P counties; (5) rate in each county was kept at P-removal rate after reduction; (6) P input was kept at the rate lower than P-offtake rate after reduction. The results showed that the total P fertilizer demand of China was 750 MT P2O5, 54% of P fertilizer can be saved from 2013 to 2080 in China, and soil Olsen-P of all counties can satisfy the demand for high crop yields. The greatest potential to decrease P input was in Yangtze Plain and South China, which reached 60%. Our results provide a firm basis to analyze the depletion of P reserves in other countries.